PENGARUH DISPLIN KERJA TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MODERASI (Studi pada Pegawai Dinas Pengendalian Penduduk Dan Keluarga Berencana Lamongan) - Mesra Surya Arifien; Arian Yusuf Wicaksono; Muhammad Dafid; Desy Wulandari (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
This research was conducted to find out whether there is an influence of work discipline on employee performance with work motivation as a moderation variable for employees of the Lamongan Population Control and Family Planning Service, this research uses quantitative methods. The population in this study was all employees of the Population Control and family planning service, which amounted to 67 employees, for sampeal in this study used a total sample where the entire population was used as a sample in the study. In this study, data management used the SPSS 26 application and MRA tests to determine the role of moderation in this study. P. The results of this study show that Work Discipline (X1) has a positive effect on Employee Performance (Y) in the Lamongan Population Control and Family Planning Service. This means that a well-managed work discipline will result in employee compliance with various organizational regulations aimed at improving performance. while Work Motivation (Z) moderates Work Discipline (X1) to Employee Performance (Y) at the Lamongan Population Control and Family Planning Service. This means that motivation is only a variable of moderation, because it weakens the influence of work discipline on employee performance